5A.01: CORONARY ATHEROSCLEROSIS AND ADVERSE OUTCOME IN HYPERTENSIVE PATIENTS WITH RECENT-ONSET ATRIAL FIBRILLATION AND TROPONIN RISE. (June 2015) - Conti, A.; Angeli, E.; Trausi, F.; Grifoni, C.; Lazzeretti, D.; Bianchi, S.; Catarzi, S.; Covelli, A.; Perrotta, M.E.; Lencioni, A.M.; Pisani, N.; Bertolini, L.
Abstract : Objective: Atrial fibrillation (AF), the most common cardiac-arrhythmia in critical-care, has reached a high prevalence in hypertensive patients. Prevention of systemic-embolism is mandatory; unfortunately, evidence to support the treatment of comorbidities as coronary artery disease (CAD) that contribute to excess mortality is lacking, and the mechanism underlying the troponin-rise during AF without acute coronary syndrome (ACS) is unclear. This study investigates the relationship between CAD, stroke and outcomes in patients with troponin-rise and AF. Design and method: Patients with a recent-onset AF and without severe comorbidities were enrolled. Baseline characteristics in those with troponin-rise versus those without were adjusted with propensity-score-matching for possible confounders. SPSS-software allowed estimation of the propensity-score using logistic-regression and specifying nearest-neighbor matching in prior-stroke, heart-rate, hypertension, TIMI-risk-score, GRACE-score, CHA2DS2Vasc-score. Patients with a troponin-rise or cardiovascular event (CVE) were considered for angiography. The primary endpoint was the composite of ACS, revascularization (with critical CAD>/ = 70%) and cardiac-death at the follow-up; the secondary endpoint was stroke. Results: Out of 6203 AF patients without severe comorbidities, 3541 with recent-onset AF completed the study; 202(6%) showed a troponin-rise, 91(3%) a CVE. After matching no difference existed in baseline characteristics. On multivariate analysis, in the entire cohort, troponin-rise, know-CAD and hypertension were predictors of the endpoint, whereas only troponin-rise (Odd Ratio, OR: 10, Confidence Interval 95%, CI: 4–22, p < 0.001) and TIMI-score > 2 (OR 4, CI 2–9, p < 0.001) in the matching cohort, suggesting the role of CAD in poor outcomes. Patients with or without troponin-rise achieved the endpoint in 38(19%) and 43(1%), respectively (p < 0.001). Stroke occurred in 4(2%) and 20 (1%), respectively (p = 0.018). Critical CAD account for 23(12%) and 15(1%), respectively (p < 0, 001). In the matching cohort, only stroke did not reach the statistical significance. Interestingly, the best cut/off troponin level for decision-making was 0.30 ng/L which, on Receiver Operator Curve analysis, was associated with 68% of sensitivity and 60% specificity; the value > 0.50 ng/L with 55% and 75%, respectively. Conclusions: Patients with a recent-onset AF and troponin-rise showed a high prevalence of CVE but not stroke, thus CAD might have a role in poor outcomes.